"Assessing the key drivers of stream network configuration dynamics for tectonically active drainage basins using multitemporal satellite imagery and statistical analyses". Issue 14 (18th August 2022) - Sajadi, Payam; Singh, Amit; Sang, Yan-Fang; Mukherjee, Saumitra; Chapi, Kamran
Abstract: A comprehensive integrated framework was designed to categorize individual streams and watersheds based on their temporal variation, and to determine the key drivers controlling watershed hydrology in the Qorveh-Dehgolan Basin. Four stream networks were extracted from multi-temporal Pan-Sharpened Landsat 7 and Landsat 8 imageries. Nineteen geomorphometric indices are measured and classified into the linear aspect, aerial aspect, and relief aspect. The results revealed a significant decline in stream networks from 2000 to 2017, reducing basin order. The factor analysis identified three principal factors including 'factor of basin magnitude' (affecting low-altitude watersheds), 'factor of steepness' (influencing high-altitude watersheds), and 'factor of texture'. The focal mechanism highlighted the complex fault mechanisms in the study area. Finally, RadViz clustering showed that for the lower order streams in the high-altitudes watersheds, stream width showed higher temporal variability in comparison to other parameters. In contrast, flow accumulation showed high variance in higher-order streams.